Evaluation of Lembang Urban Drainage System Using Drains Application - Avilla Iqbal Hisyam; Fauzia Mulyawati (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2026)
Flood is one of the main problems faced by urban areas, including Lembang. This condition often results in material losses and disrupts social and economic activities of the community. Flooding in urban areas generally occurs due to water overflow that cannot be contained by the urban drainage system such as rivers, culverts, ditches, and other water channels. Lembang, which is located in a highland area with high rainfall, is often inundated every time there is heavy rain, especially around Jalan Panorama, Lembang. Therefore, analysis and evaluation are needed to determine the causes of flooding on Jalan Panorama, Lembang based on flood discharge analysis and hydraulic analysis. From the analysis and evaluation of the urban drainage system in Lembang, it was found that at the design flood discharge for a 5-year return period (Q5), there are 10 segments of channels that cannot accommodate the flood discharge. To address this capacity issue, an improvement plan was developed through two proposed recommendations. The first recommendation is enlarging the channel dimensions using a U-ditch while maintaining the existing channel slope. The second recommendation is increasing the channel slope by deepening the channel and applying a cement plaster lining. Following the redesign process implementing these approaches, it is proven that the channels are now capable of accommodating the 5-year design flood discharge (Q5).